The real effects of EU loan guarantee schemes for SMEs: A pan-European assessment - Julien Brault; Simone Signore (European Investment Fund (EIF), 2019)
This paper provides a pan-European assessment of EU credit guarantees to SMEs. Synthesizing past research, it investigates the firm-level economic impact of over 360,000 guaranteed loans under the EU MAP and CIP programmes from 2002 to 2016. These loans represented a total amount of EUR 22bn spanning 19 European countries - approximately 60% of all loan amounts guaranteed under these programmes. The paper reports estimates of the average treatment effect on the treated of these loans on the financial growth and survivability of firms, through a comparison against SMEs that were not supported by these programmes. Guaranteed loans are found to positively affect the growth of firms' assets (by 7 to more than 35%), the share of intangible assets (by one third of the initial share in Italy and the Nordic countries), sales (by 6 to 35%), employment (by 8 to 30%), and lower their probability to default (by 4 to 5%). The paper decomposes these effects by size, age, industry, and discusses implications.
Keywords: G2; H25; O16; 330; EIF; credit guarantees; credit constraints; real effects; small and medium-sized enterprises